Reliability and Validity of the Kinect-Based Mixed Reality Device: Pilot Study - So-Young Ahn; Yun-Ho Sung; Jun-Hyun Bae; Byung-Gul Lim; Wook Song (Asian Society of Kinesiology, 2022)
OBJECTIVES Firefighter (FF) is an occupation which needs high fitness abilities. However, most of Korean FFs in the capital city have relatively low fitness levels and they have difficulty participating in exercises owing to their emergency environments. Kinect-based mixed reality device (KMR) is a device that can deliver exercises with live visual feedbacks by detecting motions at any time while needing few human resources. Therefore, KMR could be an adequate tool for FFs to provide exercise. However, there are no studies that identified the reliability and validity. So, the purpose of this study is to evaluate the reliability and validity of KMR and the intensity of the fitness program for relatively low-fit FFs. METHODS Using a test-retest design, five male participants underwent three trials with 1wk washouts. The participants underwent 1 screening and 2 workout sessions. The fitness program using KMR last approximately 25 min. Intensity was measured using the heart rate (HR), rated perceived exertion (RPE), and finger-tip lactate. HR and RPE were measured before, during, and after the exercise using the Polar watch and Borg scale. Finger-tip lactate were measured before and after the exercise using Lactate Pro2. Cronbach alpha and Pearson correlation were determined for reliability and validity based on the HR and RPE. RESULTS Excellent reliability (Cronbach alpha: 0.967, 0.969) and strong correlation (r = .525 - .814, .718 - .958; very large) were observed with regard to the HR and RPE. Additionally, HR, RPE, and post-workout lactate showed a moderate-to-high intensity response in exercise program. Conclusions The results suggest that KMR is a reliable and validate device to provide fitness programs and the fitness program designed for relatively low-fit FFs showed a "moderate-to-high" intensity response, which is an adequate physiological response for relatively low-fit Korean FFs.